REFORM AND IMPROVE THE PENSION SYSTEM IN UZBEKISTAN - Berdiyeva Umida Ubaydullayevna (Scholar Express Journals, 2022)
This article analyzes the ongoing reforms in the pension system and examines foreign experience in reforming and improving the pension system in many countries, including the Commonwealth of Independent States. In addition, proposals and recommendations have been developed for a comprehensive study of the pension system and the development of this sector in our country
Keywords: Pension; Pension Provision; Disability; Development Strategy